An Exploratory Study on Level of Competency on Mental Disorders among Police Officers’ Swat Unit in the Accra Metropolis - Asaman, A.S. (University of Ghana, 2016)
On daily basis, the police force in Ghana interacts with people, including those with mental disorders. This is one of the biggest challenges facing the police service as high expertise is required of anyone who deals with people with mental disorders. It is unfortunate though that this area remains grey and seems to be given little attention in Ghana. Several reports have also lamented the existence of very little or no scientific literature on the subject of police services` strategies in dealing with people with mental health disorders. This exploratory cross-sectional study thus sought to explore the level of competency on mental disorders among police officers in Ghana. It also explored whether officers have the capacity to identify risk factors associated with handling people with mental disorders. Systematic random sampling technique was used to select police officers for this study. The Special Weapon and Tactics (SWAT) unit was the study population. The data were processed and analysed using Microsoft Excel 2013 and STATA software version 13. Chi square was used to test the associations between the variables and odds ratio for the strength of associations. The study found very low proportion (9.5%) of police officers have ever heard of all the types of mental disorders commonly diagnosed in Ghana. Majority (97%) of the police officers were unable to mention any symptom of all the type of mental disorders commonly diagnosed in Ghana and less than 1% of them mentioned a minimum of five risk factors associated handling of people with mental disorders. Educational level of officers was found to influence the level of awareness and competency of mental disorders among police officers. The study concluded that there is low level of general awareness and competency of mental disorders among SWAT police officers in the Accra Metropolis and recommends that regular training on mental disorders should be part of the training curriculum for the police officers.
Thesis(MPH)-University of Ghana, 2016
Keywords: Mental Disorders; Police Officers’ Swat Unit; Accra Metropolis